2000
DOI: 10.1080/j.1440-1614.2000.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

The Gatehouse Project: A Systematic Approach to Mental Health Promotion in Secondary Schools

Abstract: Educational environments are complex systems undergoing continuous and simultaneous changes. The Gatehouse Project will provide unique information on the relationship between the social environment and the emotional wellbeing of young people. More importantly it outlines a sustainable process for building the capacity of schools to promote the social and emotional development of young people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 20 publications
3
61
0
1
Order By: Relevance
“…Furthermore, the absence of significant differences on the global score of stigmatizing perceptions is in line with previous research 8,21 showing that changes in attitudes are expected to occur in longer interventions, when compared to briefer ones 8,25 . Participants showed a significant decrease, from pre to post intervention, in one's intention to seek help but, on the other hand, most students moved to considering different types of help.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Furthermore, the absence of significant differences on the global score of stigmatizing perceptions is in line with previous research 8,21 showing that changes in attitudes are expected to occur in longer interventions, when compared to briefer ones 8,25 . Participants showed a significant decrease, from pre to post intervention, in one's intention to seek help but, on the other hand, most students moved to considering different types of help.…”
Section: Discussionsupporting
confidence: 73%
“…In this sense, the fact that students, after the intervention, moved to considering different types of help is considered a positive outcome. These results highlight the role of knowledge in designing interventions to promote mental health, in the sense that problems' early detection and appropriate help seeking only occur if students and significant others (family, teachers and friends) are informed about mental disorders symptoms and available resources 25 . In what concerns students' willingness to help significant others presenting a mental problem, there were no significant differences between pre and post-intervention, probably due to the fact that at pre-intervention assessment 96.2% already revealed that they would.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there has been limited success with school-based interventions, the traditional approach in which mental health professionals are reactive and remediation-oriented has not sufficiently served the school community's needs (Patton et al, 2000). Services are often fragmented and predominantly couched in assessment and consultation (Paternite, 2005).…”
Section: School-based Intervention Strategiesmentioning
confidence: 99%
“…Therefore, their involvement in the identification process is one way to ensure ownership and collaboration in providing selected and indicated programs in schools. This process needs to be time efficient because of teachers' work intensification (Patton, Glover, et al, 2000).…”
Section: Teacher Identificationmentioning
confidence: 99%